The theme of power in the performance Bum based on the drama of Marius von Mayenburg - Janowska, Aleksandra (Acta Universitatis Lodziensis. Folia Germanica, 2023)
Power is the main theme of the play Bang, which polish premiered in 2019 and took place at the New Theater of Kazimierz Dejmek in Łódź. The play was directed based on the drama of the same title, written by the contemporary German author and playwright Marius von Mayenburg. The aim of the article is to analyze and describe the means by which the viewer has the opportunity to understand why the theme of power is highlighted against the background of others presented in the play and to answer the question of what is the reason for the main character Ralf Bang’s desire to exercise power even before his own birth.